Foraminifera-bound nitrogen isotope data from Site 1241 - Jesse R Farmer; Alfredo Martínez-García; Lori Sentman; Ralf Schiebel; Anthea Arns; Maayan Yehudai; Ralf Tiedemann; Daniel M Sigman; Gerald H Haug (PANGAEA, 2025)
Early Pliocene foraminifera-bound nitrogen isotope data from ODP Site 202-1241 in Trilobatus sacculifer and combined samples of Globortalia menardii and Globortalia tumida. Full procedural replicate precision provided when measured.
In: Farmer, JR et al. (2025): Early Pliocene foraminifera-bound nitrogen isotopes and oxygen isotopic composition of seawater from ODP Sites 999 and 1241 [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.974971